MODEL PERILAKU KEPUTUSAN INVESTASI GENERASI Z DI SUMATERA UTARA: ANALISIS FINANCIAL PERSONALITY TRAITS DAN RISIKO PERCEIVED - Sally Maya Vida; Dina Hastalona (Yayasan Nusantara Hasana Berdikari, 2025)
his study aims to examine the influence of financial personality traits and risk perceived on investment decision-making behavior among Generation Z in North Sumatra. The increasing participation of young investors through digital investment platforms highlights the need to understand psychological factors that shape their financial decision-making patterns. A quantitative approach was employed, using primary data collected from 247 Generation Z respondents selected through purposive sampling. Data analysis was conducted using Structural Equation Modeling with the Partial Least Squares (SEM–PLS) method. The findings reveal that financial personality traits have a significant and positive effect on investment decision-making behavior, indicating that self-control, risk tolerance, and future orientation serve as key determinants of investment choices among young investors. Risk perceived also shows a significant effect, demonstrating that higher levels of perceived risk tend to reduce the likelihood of making aggressive investment decisions. The model explains 48,7% of the variance in investment decision-making behavior, indicating strong explanatory power. This research contributes empirical evidence that psychological factors play a critical role in shaping the investment behavior of Generation Z, particularly in emerging regional contexts such as North Sumatra. The findings are expected to support the development of more adaptive and personality-based financial literacy strategies and provide direction for future studies to incorporate broader contextual variables.